Comparative efficacy and acceptability of psychosocial interventions for PTSD, depression, and anxiety in asylum seekers, refugees, and other migrant populations: a systematic review and network meta-analysis of randomised controlled studiesResearch in context - Giulia Turrini; Marianna Purgato; Camilla Cadorin; Monica Bartucz; Doriana Cristofalo; Chiara Gastaldon; Michela Nosè; Giovanni Ostuzzi; Davide Papola; Eleonora Prina; Federico Tedeschi; Anke B. Witteveen; et al. (Elsevier, 2025)
Summary: Background: Migrant populations are at increased risk of developing mental health problems. We aimed to compare the efficacy and acceptability of psychosocial interventions in this population. Methods: We conducted a systematic review and network meta-analysis (NMA). Cochrane Central Register of randomised trials (CENTRAL), MEDLINE, PTSDpubs, PsycINFO, PubMed, CINAHL, EMBASE, Web of Science, Scopus, and ClinicalTrials.gov were searched from database inception to October 7, 2024, to identify randomized clinical trials assessing the efficacy of psychosocial interventions for migrant populations in reducing symptoms of post-traumatic stress disorder (PTSD), depression or anxiety. Studies with second-generation migrants were excluded if they comprised over 20% of participants. Two independent researchers screened, reviewed, and extracted data. The primary outcomes were the severity of PTSD, depression, and anxiety symptoms at post-intervention. Secondary outcomes included acceptability. Standardised mean differences (SMDs) and risk ratios (RRs) were pooled using pairwise and NMA. PROSPERO: CRD42023418817. Findings: Of the 103 studies with 19,230 participants included, 96 contributed to the meta-analyses for at least one outcome, with women representing 64% of the participants. Narrative Exposure Therapy (NET), counselling, Eye Movement Desensitization and Reprocessing (EMDR), and creative expressive interventions demonstrated greater efficacy than treatment as usual (TAU) in reducing PTSD symptoms, with SMDs [95% Confidence Intervals (CIs)] ranging from −0.69 [−1.14, −0.24] to −0.60 [−1.20, −0.01], albeit with low confidence in the evidence. For depressive symptoms, Integrative therapy emerged as the top intervention compared to TAU, with moderate confidence (SMD [95% CI] = −0.70 [−1.21, −0.20]). For anxiety symptoms, NET, Integrative therapy, and Problem Management Plus (PM+)/Step-by-Step (SbS) were more effective than TAU, with SMDs [95% CIs] ranging from −1.32 [−2.05, −0.59] to −0.35 [−0.65, −0.05]. Still, the confidence in the evidence was low. Overall, head-to-head comparisons yielded inconclusive results, and the acceptability analysis revealed variations across interventions. 16% of the studies (17 studies) were classified as "high risk" of bias, 68% (70) as having "some concerns", and 18% (19) as "low risk". We identified considerable heterogeneity (I2 of >70%). Interpretation: The analysis revealed no clear differences in the efficacy of psychosocial interventions compared to TAU for reducing symptoms of PTSD, depression, and anxiety. While certain interventions showed potential benefits, confidence in these findings was generally low, limiting the ability to draw definitive conclusions about their comparative effectiveness. Funding: This research received no specific grant from any funding agency.